Jaring Pengaman Sosial: Analisis Anggaran Penanganan COVID-19 di Aceh - Vellayati Hajad; Ikhsan Ikhsan; Nodi Marefanda (Journal of Governance and Social Policy, 2021)
This study discusses the budget for handlingCOVID-19 in Aceh Province with a Social Safety Net approach. Through this Social Safety Network approach, the Aceh Government has allocated a budget for handlingCOVID-19 is intended to be given to acehnese people who are directly affected from COVID-19. While the purpose of this study is to find out the extent of the success of the budget for handlingCOVID-19 is realized to the public to rise from the crisis during theCOVID-19 pandemic. This research is an exploratory descriptive qualitative method research to explain and dig up information about the budget for handlingCOVID-19 by answering various types of questions and problems that occur and are identified and analyzed based on the results of readings and interpretation data related to the research theme. The results showed that the budget for handlingCOVID-19 in Aceh Province in the Social Safety Net sector was already running and the affected Acehnese people had received social assistance provided by the Aceh Government. However, there needs to be supervision from the people of Aceh in order for transparency in the management of theCOVID-19 budget. In addition, in anticipation that the practice of corruption in handling theCOVID-19 budget in the Aceh Government environment can be prevented.